GABA A but not GABA B receptors in the lateral hypothalamus modulate the tachycardic response to emotional stress in rats - Gomes-de-Souza, Lucas [UNESP]; Benini, Ricardo [UNESP]; Costa-Ferreira, Willian [UNESP]; Crestani, Carlos C. [UNESP] (Elsevier, 2019)
The lateral hypothalamus (LH) has been described as one of the hypothalamic areas involved in the behavioral and physiological responses triggered by aversive stimuli. Previous studies indicated involvement of the LH in cardiovascular responses to stress. Despite this evidence, the local neurochemical mechanisms involved in LH control of stress responses is still poorly understood. Therefore, in the present study, we investigated the role of GABAergic neurotransmission within the LH in cardiovascular responses induced by an acute session of restraint stress in rats. For this, we evaluated the effect of bilateral microinjection of selective antagonists of either GABA A or GABA B receptors into the LH on arterial pressure increase, heart rate (HR) increase and reduction in tail skin temperature induced by restraint stress. We found that microinjection of the selective GABA A receptor antagonist SR95531 into the LH decreased the increase in HR caused by restraint stress, but without affecting the increase in arterial pressure increase or the reduction in tail skin temperature. Conversely, LH treatment with the selective GABA B receptor antagonist CGP35348 did not affect the restraint-evoked cardiovascular changes. These findings indicate that GABAergic neurotransmission in the LH, acting through activation of local GABA A receptors, plays a facilitatory role in the tachycardic response observed during aversive threats.
Keywords: Blood pressure; GABAergic neurotransmission; Heart rate; Hypothalamus; Restraint stress; Sympathetic activity